Comparative acceptability of saliva-based self-testing versus blood-based self-testing for HIV screening among key populations in Kisangani - Tagoto, Tepungipame; Tonen-Wolyec, Serge; Panda, Lukongo; Batina, Agasa; Falay, Sadiki; Losimba, Likwela (BMC infectious diseases, 2024)
HIV self-testing represents a convenient and confidential option for HIV testing-the present study aimed to assess the acceptability of blood versus saliva self-tests among key populations in Kisangani. This study was an analytical cross-sectional study. Our sample size was 363 subjects. After obtaining their consent, we administered a questionnaire to participants. We asked participants to choose between blood and saliva self-testing. We defined the acceptability of the self-test (saliva or blood) as the intention to use the self-test using a 5-point Likert scale. Descriptive statistics were described by estimating proportions for categorical variables and means with standard deviations for symmetrically distributed quantitative variables. The variable of interest was the acceptability of self-testing, which was dichotomized (Very Likely/Unlikely). The corresponding endpoint was the proportion of participants accepting the self-test in HIV screening. A bivariate analysis was performed to determine factors related to the acceptability of the self-test, using Pearson's Chi-square (χ2) and ANOVA followed by 2-to-2 multiple comparisons (Bonferroni) for comparison of means and proportions. A progressive stepwise logistic regression model at the 5% threshold included variables with a bi-variate association. The acceptability of the blood self-test was 71.6% compared to 28.4% for the saliva self-test. Factors associated with acceptability of the self-test were higher level of education aOR CI95%: 1.5(0.4-5.5) p = 0.006; non-use of condoms with casual partners aOR CI95%: 2.8(1.4-5) p = 0.003; knowledge of the type of self-test aOR CI95%:2.4(1.02-5.65) p = 0.043 and the obstacle to acceptability of the self-test was non-availability of the self-test aOR CI 95%: 18.9(6.5-54.9) p < 0.0001. Our study showed that key populations in Kisangani preferred blood self-testing over saliva self-testing. Blood self-tests must be made available to key population groups, as this would improve access to testing for these populations, thus boosting the first UNAIDS target 95.